Generation of controllable magnetic stimuli - Denison, T; Rogers, DJ; Memarian Sorkhabi, M (World Intellectual Property Organization, 2021)
A stimulation circuit generates magnetic stimulation for application to a body organ using a coil arrangement. A DC supply is provided and supplied to a DC/AC inverter that comprises a bridge inverter stage comprising plural switch modules connected in a bridge arrangement between input terminals and output terminals for supplying the stimulation signal. A driver circuit supplies pulse width modulation control signals to the switch modules that are selected to control the DC/AC inverter to generate the stimulation signal with pulse width modulation of voltage, thereby providing for a high degree of control of the form of the stimulation.